G-protein coupled purinergic P2Y12 receptor interacts and internalizes TauRD-mediated by membrane-associated actin cytoskeleton remodeling in microglia - Chidambaram, Hariharakrishnan; Das, Rashmi; Chinnathambi, Subashchandrabose (European Journal of Cell Biology, 2022)
In Alzheimer’s disease, the microtubule-associated protein, Tau misfolds to form aggregates and filaments in the intra- and extracellular region of neuronal cells. Microglial cells are the resident brain macrophage cells involved in constant surveillance and activated by the extracellular deposits. Purinergic receptors are involved in the chemotactic migration of microglial cells towards the site of inflammation. From our recent study, we have observed that the microglial P2Y12 receptor is involved in phagocytosis of full-length Tau species such as monomers, oligomers and aggregates by actin-driven chemotaxis. This study shows the interaction of repeat-domain of Tau (TauRD) with the microglial P2Y12 receptor and the corresponding residues for interaction have been analysed by various in-silico approaches. In the cellular studies, TauRD was found to interact with microglial P2Y12R and induces its cellular expression confirmed by co-immunoprecipitation and western blot analysis. Furthermore, the P2Y12R-mediated TauRD internalization has demonstrated activation of microglia with an increase in the Iba1 level, and TauRD becomes accumulated at the peri-nuclear region for the degradation. Similarly, immunofluorescence microscopic studies emphasized that TauRD is phagocytosed by microglial P2Y12R via the membrane-associated actin remodeling as filopodia extension. Upon internalization, we have demonstrated the P2Y12R signaling-mediated degradation of accumulated TauRD by lysosomal pathway. Altogether, microglial P2Y12R interacts with TauRD and mediates directed migration and activation for its internalization and degradation.
Keywords: Alzheimer’s disease; Internalization; microglia; P2Y12R; Phagocytosis; Tau